Penerapan Kebijakan Pendidikan Di Indonesia - Shelvia Permata Sari; Rida Ramadhani Ritonga; Budi Askhori Sirait (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Education plays an important role in the progress of the nation and state. In the development of the country's national education, it certainly requires policies that are able to make education more advanced. The role of policy itself is very crucial because it can help someone make decisions by providing information collected through research and analysis processes, classifying and clarifying problems that reveal discrepancies in goals and efforts, suggesting new possibilities and suggesting how to interpret ideas or ideas into a policy that is easy to implement and implemented. After policy making is carried out, of course it is necessary to apply or implement it to see the results of the policy. The purpose of implementing the policy itself is to set a direction so that the policy objectives can be implemented. The purpose of this study is to analyze the application of policies in the education system itself by reviewing the stages and approaches in implementing educational policies.